Peran Guru BK dalam Pelaksanaan Bimbingan dan Konseling serta Mengatasi Kenakalan Siswa di SMA IT Raudhatul Ulum Sakatiga Kabupaten Ogan Ilir - Fitri Susanty (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2022)
Guidance and counseling services in schools is an effort to help students in the development of personal life, social life, learning activities, as well as planning and career development. Guidance and counseling services facilitate the development of students individually, in groups, and or classically, according to their needs, potential, talents, interests, developments, conditions, and opportunities. This service also helps overcome weaknesses and obstacles as well as problems faced by students. This research was conducted at IT Raudhatul Ulum Sakatiga High School, Ogan Ilir Regency and carried out from March to June 2022. This study aims to determine the implementation of the guidance and counseling program for students at IT Raudhatul Ulum Sakatiga High School and to determine the role of BK teachers in the implementation of the guidance and counseling program. counseling and overcoming student delinquency at SMA IT Raudhatul Ulum, Sakatiga Village, Indralaya Ogan Ilir District. This type of research is descriptive qualitative research tells a situation to draw a conclusion. The data sources of this research are primary and secondary data, informants in this study are school principals, Guidance and Counseling teachers, students, homeroom teachers, and student affairs administrators. The instrument of data collection in this study was interviews, observation, and documentation. Based on the results of this study, it was concluded that the implementation of the guidance and counseling program at SMA IT Raudhatul Ulum Sakatiga had been going well. This happens because of the cooperation between the BK teacher and the principal as well as with teachers of other subjects. The role of BK teachers in overcoming problematic students, providing advice, guidance, assistance, directing, and giving warnings. While the efforts that have been made are preventive, repressive and curative efforts.